1997
DOI: 10.2337/diacare.20.4.632
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Acting Somatostatin Analog (Somatulin) on Renal Hyperfiltration in Patients With IDDM

Abstract: The administration of long-acting Somatulin to patients with IDDM and renal hyperfiltration leads to only a temporary reduction of ERPF/GFR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…To the contrary, octreotide has been shown to decrease renal growth, and when combined with captopril, to reduce urinary albumin excretion as much as insulin treatment in established diabetes (17). In humans with diabetes, a small short-term (3-wk) study of octreotide treatment reported a decrease in glomerular hyperfiltration, but a longer term (9-mo) study showed no sustained benefit (25,48).…”
Section: Discussionmentioning
confidence: 99%
“…To the contrary, octreotide has been shown to decrease renal growth, and when combined with captopril, to reduce urinary albumin excretion as much as insulin treatment in established diabetes (17). In humans with diabetes, a small short-term (3-wk) study of octreotide treatment reported a decrease in glomerular hyperfiltration, but a longer term (9-mo) study showed no sustained benefit (25,48).…”
Section: Discussionmentioning
confidence: 99%
“…The strong inhibitory effect on GH and IGF-I secretion also makes SOM230 a candidate drug for the treatment of other diseases such as diabetes-induced complications like micro-and macroangiopathy (38 -41) where, according to the GH hypothesis, the overproduction of GH is a causal factor in the development of proliferative angiopathy (for review see 42). In addition, Sandostatin has been shown previously to decrease the glomerular filtration rate (GFR) in diabetes-associated renal hyperfiltration (43). Therefore, an SRIF analog that even more effectively suppresses the release of GH and IGF-I may have a therapeutic advantage over the currently available SRIF analogs in such indication.…”
Section: Discussionmentioning
confidence: 99%
“…The first Sst analogues used in diabetic conditions were lanreotide (Somatuline) to treat renal hyperfiltration and octreotide to counteract vascular endothelial dysfunction. This latter drug soon was proved to be effective in delaying or to some extent reversing symptoms of DR .…”
Section: Anti‐dr Drug Treatments Used Currently In Clinical Practicementioning
confidence: 99%